Tarjouksen tarjouspyynnön mukaisuus 4 D - Ukkola, Markus (Lakimies, 2025)
Conformity between the tender and the procurement documents in 4D Provisions on whether a tender meets the requirements set out in the procurement documents form an important and established theme within public procurement law. The everyday nature of this theme may have led to a conception among legal professionals that legal questions relating to it are quite settled. However, the author submits that this theme has many more dimensions than what is usually considered. The basic mechanism is one similar to a legal syllogism: An issue of conformity between the minor premise of information in a tender and the major premise, or a standard, formed by the requirements in the procurement documents. The major premise can, however, include a large variety of types of requirement. They can be substantive (requirements regarding the object of the procurement or requirements regarding bidders) or they can deal with formalities of evidence or tender. Mixing the different types of requirements can lead to problems in assessing whether there is conformity. The issue of conformity between the tender and the procurement documents also has a temporal dimension. The point of time when to assess the conformity between the tender and the procurement documents may vary according to the nature of the requirement in question. Finally, there is the dimension of asking the tenderers to clarify or supplement incomplete or erroneous information in their tenders. The chances of asking for clarifications or additions vary according to what kind of incomplete or erroneous information is in question. Being aware of these dimensions may help legal professionals to see the issue of conformity between the tender and the procurement documents in a more comprehensive way.